EXPLORING SEASONAL DYNAMICS: PHYSICO-CHEMICAL TRAITS OF THUNGA AND BHADRA RIVERS IN KARNATAKA, INDIA - 1Muruganantham Manickam, 2Amutha Meenakshi Sundaram, 3Pushparaj Arunachalam, 4Senthil Nathan Sengottayan (Chelonian Research Foundation, 2023)
The aim of the present study is to investigate the water quality of the Thunga Bhadra River, a significant tributary of the Krishna River Basin in Karnataka, India.The surface water samples were put through a thorough Physico-Chemical investigation that included significant cations and anions in addition to general characteristics. The Water variables were plottedin spatial map using GIS and analysed by Pearson correlation. The temperature, pH, Dissolved oxygen, Electrical Conductivity, Hardness, Alkalinity, Turbidity, Total solids, Total suspended solids, Total dissolved solids, DO, BOD and COD. Most of the parameters like pH, conductivity, Turbidity; Dissolved solids are high at Bhadra riverduring the Monsoon in India. It is suggested that the Bhadra river possess highly fertile undisturbed water environment value Keywords: Physico-chemical, PCA, Monsoon, Post monsoon, Pre monsoon, Thunga and Bhadra Rivers